The regeneration-responsive element careg monitors activation of Müller glia after MNU-induced damage of photoreceptors in the zebrafish retina - Bise, Thomas; Pfefferli, Catherine; Bonvin, Marylène; Taylor, Lea; Lischer, Heidi E. L.; Bruggmann, Rémy; Jaźwińska, Anna (Frontiers in Molecular Neuroscience, 2023)
In contrast to mammals, zebrafish can regenerate their damaged photoreceptors. This capacity depends on the intrinsic plasticity of Müller glia. Here, we identified that the transgenic reporter careg, a marker of regenerating fin and heart, also participates in retina restoration in zebrafish. After methylnitrosourea (MNU) treatment, the retina became deteriorated and contained damaged cell types including rods, UV-sensitive cones and the outer plexiform layer. This phenotype was associated with the induction of careg expression in a subset of Müller glia up until the reconstruction of the photoreceptor synaptic layer. scRNAseq analysis of regenerating retinas revealed a population of immature rods, defined by high expression of rhodopsin and the ciliogenesis gene meig1, but low expression of phototransduction genes. Furthermore, cones displayed deregulation of metabolic and visual perception genes in response to retina injury. Comparison between careg:EGFP expressing and non-expressing Müller glia demonstrated that these two subpopulations are characterized by distinct molecular signatures, suggesting their heterogenous responsiveness to the regenerative program. Dynamics of ribosomal protein S6 phosphorylation showed that the TOR signaling became progressively switched from Müller glia to progenitors. Inhibition of TOR with Rapamycin reduced the cell cycle activity, but neither affected careg:EGFP expression in Müller glia, nor prevented restoration of the retina structure. This indicates that Müller glia reprogramming, and progenitor cell proliferation might be regulated by distinct mechanisms. In conclusion, the careg reporter detects activated Müller glia, and provides a common marker of regeneration-competent cells in diverse zebrafish organs, including the retina.